Anticancer Activities of New N-hetaryl-2-cyanoacetamide Derivatives Incorporating 4,5,6,7-Tetrahydrobenzo[b]thiophene Moiety - F. Mohamed, Magda; M. Attia, Yasmin; A. Shouman, Samia; A. Abdelhamid, Ismail (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Aims: Novel series of N-(4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl) cyanoacetamide derivatives are synthesized. Method: The structure of these compounds was elucidated using different spectral tools. Compounds were evaluated for their cytotoxic activities against different types of human cancer cell lines including, breast (MCF-7, T47D, MDA MB231); liver (HEPG-2); colon (HCT116); prostate (PC3); and cervix (HELA) cells. In this study, we used compounds 11 and 12 that showed the highest cytotoxicity on PC3 and HEPG2 cells, to explore their effects on apoptosis, metastasis and angiogenesis of cancer cells. Results: Results revealed that the growth inhibition produced by the two selected compounds was due to cytocidal and not due to cytostatic effect in both cell lines. This cytocidal effect was due to up-regulation of caspases-3, and- 9. In addition, the two compounds inhibited the expression of metalloproteinases-2 and 9 (MMP 2&9). Moreover, HIF-1alpha and VEGF expressions were inhibited by both compounds. Conclusion: In conclusion, N-(4, 5, 6, 7-tetrahydrobenzo[b]thiophen-2-yl) cyanoacetamide derivatives showed different anticancer potential against different cancer cell lines. Compounds 11 and 12 showed the most active cytotoxicity against PC3 and HepG2 cells. Both compounds have apoptotic, anti- metastatic and anti-angiogenic effects.
Keywords: VEGF